In-situ cross-linking strategy for efficient and operationally stable methylammoniun lead iodide solar cells - Li, Xiaodong; Zhang, Wenxiao; Wang, Ying-Chiao; Zhang, Wenjun; Wang, Hai-Qiao; Fang, Junfeng (Nature communications, 2018)
Long-term operational stability is the foremost issue delaying the commercialization of perovskite solar cells (PSCs). Here we demonstrate an in-situ cross-linking strategy for operationally stable inverted MAPbI 3 PSCs through the incorporation of a cross-linkable organic small molecule additive trimethylolpropane triacrylate (TMTA) into perovskite films. TMTA can chemically anchor to grain boundaries and then in-situ cross-link to a robust continuous network polymer after thermal treatment, thus enhancing the thermal, water-resisting and light-resisting properties of organic/perovskite films. As a result, the cross-linked PSCs exhibit 590-fold improvement in operational stability, retaining nearly 80% of their initial efficiency after continuous power output for 400 h at maximum power point under full-sun AM 1.5 G illumination of Xenon lamp without any UV-filter. In addition, under moisture or thermal (85 °C) conditions, cross-linked TMTA-based PSCs also show excellent stability with over 90% of their initial or post burn-in efficiency after aging for over 1000 h. The stability of perovskite solar cell remains the biggest challenge that hinders its commercialization. Here Li et al. incorporate crosslinkable molecules to form a crosslinked perovskite film and increase the device operational stability by 590 times to 400 h under standard Xenon lamp without filters.